2008
DOI: 10.3382/japr.2008-00062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Initial Full Feeding of Broiler Breeder Pullets on Carcass Development and Body Weight Variation

Abstract: Broiler breeder pullets are fully fed for several weeks to give chicks a vigorous start, to establish an adequate frame size, and to build increased flock BW uniformity. This study was designed to determine whether reducing the length of the initial ad libitum feeding period of pullets would be detrimental to subsequent fleshing, skeletal development, and BW variation. A total of 720 Ross 308 pullets were placed in 8 pens on the day of hatch and provided ad libitum access to feed at 1 wk (1WK) or 3 wk (3WK) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Although we used a correction factor (Romero et al, 2009a) to account for this correlation directly in the model, the existence of this positive correlation indicates that the correction factor underestimated the effect of feed intake on MEm observed in the current study. Pishnamazi et al (2008) reported that feed intake level had a positive relationship with MEm energy expenditure in broiler breeder pullets (R 2 = 0.95). Herd and Arthur (2009) also demonstrated that as feed intake increased, the energy expenditure to digest the feed increased.…”
Section: Energetic Efficiencymentioning
confidence: 98%
“…Although we used a correction factor (Romero et al, 2009a) to account for this correlation directly in the model, the existence of this positive correlation indicates that the correction factor underestimated the effect of feed intake on MEm observed in the current study. Pishnamazi et al (2008) reported that feed intake level had a positive relationship with MEm energy expenditure in broiler breeder pullets (R 2 = 0.95). Herd and Arthur (2009) also demonstrated that as feed intake increased, the energy expenditure to digest the feed increased.…”
Section: Energetic Efficiencymentioning
confidence: 98%
“…Feed intake has been found to be positively correlated to ME m [10]. Through reduced feed intake ME m is decreased [10]. This theory supports that the reduction in ME m during the 8-16 period is due to feed restriction relative to ad libitum.…”
Section: Discussionmentioning
confidence: 54%
“…Studies estimated that at 9-20 weeks of age, 95-96% of total ME intake was used for maintenance whereas from 5-8 weeks 72.5% was utilized for maintenance [9]. Feed intake has been found to be positively correlated to ME m [10]. Through reduced feed intake ME m is decreased [10].…”
Section: Discussionmentioning
confidence: 99%
“…The mathematical model used to predict energy partitioning to HP and RE was based on previous work of Romero et al. (2009) and used by others ( Pishnamazi et al., 2008 , Hadinia et al., 2018 ). The following model was defined in the NLMIXED procedure in SAS (version 9.4.; SAS Institute Inc., Cary, NC, 2012): MEI d = ( a + u ) × BW b + c × BW d × ADG e + ε, u ∼ N (0, V u ), MEI d ∼ N (μ,V), where MEI d = daily ME intake (kcal/D), BW = body weight (kg), ADG = average daily gain (g/D) calculated over a 4-D period, ε = residual error.…”
Section: Methodsmentioning
confidence: 99%